Clinicopathological study of testicular lesions - Dhawle, Manjusha; Tangde, Ashwini; Joshi, Anil; Bindu, Rajan (International Journal of Research in Medical Sciences, 2019)
Background: Testis is affected by both neoplastic and non neoplastic conditions. Non neoplastic lesions of the testis include epididymo-orchitis, testicular atrophy, undescended testis, testicular abscess etc. Testicular tumors are relatively rare. They constitute the 4th most common cause of death from neoplasia in the young males. This study was undertaken to study the histopathological spectrum, age wise distribution and clinical symptoms of testicular lesions. Methods: This is a retrospective study of three years conducted in the department of pathology, Aurangabad from June 2015 to May 2018. It included all the orchidectomy specimens received from the department of surgery and excluded the orchidectomy specimens sent for infertility and prostatic carcinoma. A detail clinical history was taken. Histopathological examination was done after routine processing and staining with H and E. The data collected was tabulated, analysed and compared to other similar studies. Results: We studied 70 cases. Non neoplastic testicular lesions were 57 and 13 were neoplastic. Non neoplastic testicular lesions were more common than the neoplastic ones. Non neoplastic testicular lesions presented most commonly in the 2nd decade. Most common non neoplastic lesion was epididymo-orchitis followed by torsion, atrophy and testicular abscess. Most common neoplasm was malignant mixed germ cell tumor. Most of the patients of neoplasms presented in the 3rd decade. The most common complaint was testicular swelling and pain. Conclusions: Majority of testicular lesions are non neoplastic. Neoplastic lesions are rare. Non neoplastic lesions mimic neoplastic ones clinically, as testicular swelling is the most common complaint. So histopathological diagnosis is necessary for an accurate diagnosis of testicular lesions.